DOMAIN NAME IN THE SYSTEM OF OBJECTS OF INTELLECTUAL PROPERTY RIGHTS - Filinovych, Valeriia; Sukhanov, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: study the actual problem of determining the place of domain names in the system of objects of intellectual property rights. The methodological basis: generally recognized methods of scientific knowledge, namely: analytical, comparatively legal, systemically structural and others. Results: the definition of the concept of a domain name in the current Ukrainian legislation was studied, a comparative analysis of the concepts of «trademark» and «domain name» was carried out, and topical problematic issues of methods and means of protecting a domain name as a separate object of intellectual property rights and as an object of different legal branches were identified, and also the suggestions for overcoming such issues were presented. Discussion: the discussion in the study is devoted to finding methods to solve the problem of determining the place of domain names in the system of objects of intellectual property rights and methods and means of protecting domain names as separate objects of intellectual property rights.